Effects of site preparation and reindeer grazing on the early-stage success of Scots pine regeneration from seeds in northern Finland and Sweden - Miettinen, Janne; Hallikainen, Ville; Hyppönen, Mikko; Bergsten, Urban; Winsa, Hans; Välikangas, Pekka; Hiltunen, Arto; Aatsinki, Pasi; Rautio, Pasi
2022